2019
DOI: 10.1186/s12955-018-1069-6
|View full text |Cite
|
Sign up to set email alerts
|

The combined impact of dependency on caregivers, disability, and coping strategy on quality of life after ischemic stroke

Abstract: BackgroundTo estimate the additional impact of coping and of being dependent on caregivers, over and above the large effects of disability on utility after ischemic stroke.MethodsA total of 539 patients were recruited into an observational, retrospective study when returning for a check-up between 3 and 36 months after an ischemic stroke. Patients’ modified Rankin Scale (mRS), dependency on caregivers, the Brandtstädter and Renner Coping questionnaire (with summary scores: Tenacity of Goal Pursuit (TGP) and Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
2
17
0
3
Order By: Relevance
“…Only studies that reported the sample size in addition to the mean and SD or SE of the mean for each mRS score and utility weights at each mRS score were included in the meta-analysis. Nine studies 13,16,25,36,37,[43][44][45]47 using the EQ-5D (n = 9607), 5 studies 31,[38][39][40]48 using the SIS (n = 777), and 1 study each using the SF-36-PF (n = 278), 27 SF-36-SF (n = 278), 27 World Health Organization Global Burden of Disease Project (n = 54), 28 Statistically significant differences were observed between the mean utility weights by mRS score for all health utility scales evaluated (Figure 2). For studies using an EQ-5D-weighted mRS score, between-study variance was higher for worse (mRS 2-5) compared with better (mRS 0-1)…”
Section: Resultsmentioning
confidence: 99%
“…Only studies that reported the sample size in addition to the mean and SD or SE of the mean for each mRS score and utility weights at each mRS score were included in the meta-analysis. Nine studies 13,16,25,36,37,[43][44][45]47 using the EQ-5D (n = 9607), 5 studies 31,[38][39][40]48 using the SIS (n = 777), and 1 study each using the SF-36-PF (n = 278), 27 SF-36-SF (n = 278), 27 World Health Organization Global Burden of Disease Project (n = 54), 28 Statistically significant differences were observed between the mean utility weights by mRS score for all health utility scales evaluated (Figure 2). For studies using an EQ-5D-weighted mRS score, between-study variance was higher for worse (mRS 2-5) compared with better (mRS 0-1)…”
Section: Resultsmentioning
confidence: 99%
“…23 In another study by Dewilde et al, it was found that patients' QOL after a stroke is dictated by their disability, level of dependence on caregivers, and coping strategy. 24 The added obligation of taking care of a disabled stroke survivor along with adjusting their own lifestyle with financial apprehensions, worry about future, prolonged hours of care, and stress are major factors that increase the burden of the caregivers. Several other studies have published similar results.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In another study by Dewilde et al, it was found that patients' QOL after a stroke is dictated by their disability, level of dependence on caregivers, and coping strategy. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke, accounting for approximately 80% of all strokes, is one of the major causes of disability [ 1 , 2 ]. Even when stroke symptoms are stabilized, stroke survivors’ daily lives are still seriously affected [ 3 ]. The goal of stroke rehabilitation is to help patients restore physical and mental functions, and relearn the necessary skills to live everyday life.…”
Section: Introductionmentioning
confidence: 99%